2018
DOI: 10.1016/j.nicl.2018.03.035
|View full text |Cite
|
Sign up to set email alerts
|

The association of regional white matter lesions with cognition in a community-based cohort of older individuals

Abstract: Emerging evidence from lesion-symptom mapping (LSM) studies suggested that regional white matter lesions (WML) on strategic white matter (WM) fiber tracts are significantly associated with specific cognitive domains, independent of global WML burden. However, previous LSM investigations were mostly carried out in disease cohorts, with little evidence from community-based older individuals, making findings difficult to generalize. Moreover, most LSM studies applied a threshold to the probabilistic atlas, leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 36 publications
7
39
0
Order By: Relevance
“…As AD is characterized by a number of neurodegenerative changes that gradually lead to global cognitive impairment, when concurrent major WM pathology develops, the cognitive impairments following from these two pathologies appear to be cumulative in some respects. The fact that we did not see the same association in the control group is somewhat surprising [44,48] but could be due to differences in group size, participant age, or WMH extent.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…As AD is characterized by a number of neurodegenerative changes that gradually lead to global cognitive impairment, when concurrent major WM pathology develops, the cognitive impairments following from these two pathologies appear to be cumulative in some respects. The fact that we did not see the same association in the control group is somewhat surprising [44,48] but could be due to differences in group size, participant age, or WMH extent.…”
Section: Discussionmentioning
confidence: 62%
“…Strengths of the present study include using several validated neuropsychological tests for cognitive measurements and utilizing quantified measures for MRI analysis, although it should be stated that higher-resolution MRI has been utilized in a number of previous studies [8,48,50]. Furthermore, the sample size is not ideal due to many participants being excluded.…”
Section: Discussionmentioning
confidence: 99%
“…(Longstreth et al, 1996) and are thought to have a vascular etiology, although their histopathological substrate might be heterogeneous as shown by pathological studies (Mortamais, Artero, & Ritchie, 2014;Prins & Scheltens, 2015) as well as by microstructural characterization of WMH with diffusion-weighted MRI imaging (Bastin et al, 2009;Wardlaw, Valdés Hernández, & Muñoz-Maniega, 2015;Zhong & Lou, 2016). Even they are relatively frequent in asymptomatic individuals (Arvanitakis et al, 2016;Birdsill et al, 2014;Brugulat-Serrat et al, 2017;Kloppenborg, Nederkoorn, Geerlings, & van den Berg, 2014), WMH burden has been shown to exert a negative impact on cognition (Arvanitakis et al, 2016;Bolandzadeh, Davis, Tam, Handy, & Liu-Ambrose, 2012;Jiang et al, 2018;Lampe et al, 2017) mainly in executive function (EF) (Desmond, 2002;de Groot et al, 2000;Jiang et al, 2018;Kloppenborg et al, 2014;Ramirez, McNeely, Scott, Stuss, & Black, 2014). WMH also increase the risk of cognitive decline and Alzheimer's disease (AD), contributing to its progression and severity (Habes et al, 2016;Smith et al, 2008).…”
mentioning
confidence: 99%
“…A meta-analysis of MRI studies also concluded that, although the effect sizes were small, lower levels of physical fitness and activity are associated with lower white matter volume, and increased white matter lesion volume and severity [24]. These changes in white matter have, in turn, been associated with poorer cognitive function [25][26][27]. Interim analysis of the large Dr's Extra intervention study, involving 1,335 older people, found that moderate to high levels of fitness predicted > 50%lower incidence of memory impairment than low fitness; however, it failed to show any group effect of exercise on cognition [28].…”
Section: Introductionmentioning
confidence: 99%